Achieving sustainable coastal environment in Langkawi, Malaysia - Mazlin, Mokhtar *; Minhaz, Farid Ahmed; Lee, Khai Ern *; Lubna, Alam; Goh, Choo Ta; Rahmah, Elfithri; Jamil, Tajam; Wong, Anthony Kim Hooi (University of Sabah Malaysia, 2017)
Despite many good policies and institutions, the coastal environment of Langkawi continues to deteriorate. This could be due to lack of effective governance as well as unregulated waste discharge. Evidences collected from the literature during 1996 to 2013 also revealed a significant increase in the concentrations of Zn (R2 = 0.78) and Pb (R2 = 0.12) in the sediment. This appears to be the result of large volume of terrestrial runoff that brings these metals originating from extensive anthropogenic activities. It is a vital indicator of coastal pollution. It is a matter of concern that in many cases Pb concentration in the sediment exceeded the world average value 20 µg/g as well as Canadian Interim Sediment Quality Standard of 35 µg/g for the coastal areas. Similarly, the metal pollution index (MPI) measured over a period of 2007 to 2009 in fish also indicated an increasing trend of pollution in Langkawi. The maximum MPI value (4.87) was recorded in Spanish mackerel. Since pollution of coastal environment has serious implications for marine biodiversity and health of seafood consumers, measures are required to address this problem. Use of constructed wetland might be effective in reducing the coastal pollution as this will filter the effluent and waste before their mixing with the coastal water. Furthermore, enabling the stakeholders to play the environmental stewardship role will ensure better governance of coastal ecosystem and effective implementation of policies, envisaging an improved monitoring of waste/effluent discharge into the coastal marine environment. These measures are among the actions necessary for achieving a sustainable coastal environment of Langkawi.